REGIMENTAL PRISON IN HETMANATE: APPEARANCE AND CONDITION OF BUILDING IN THE MIDDLE OF THE XVIII CENTURY (City: History, Culture, Society, 2018)
The article attempts to investigate a condition of the buildings for the prisoners and guardians in the middle of the XVIII century in the regimental prisons of the Hetmanate and in Hlukhiv. The prison was an essential public building in the early modern towns. The excellent condition of the walls of the jail was a guarantee of successful punishment for the thieves and the prevention of new offences.In the legal sources (in the Statutes of Lithuania and in the Laws by Which the Little Russian People Are Judged), there are three types of places where prisoners could be held – the “lower” and “upper” prisons and a separate room for convicted prisoners. The appearance of prisons in domestic historiography is poorly researched and untold. The studies indicate that various types of buildings were used as a prison, such as a hut, a shed. However, sometimes researchers mentioned the prisons with a binary structure (upper and lower).Typically, in criminal proceedings, the appearance of prisons was not reported. If the court session ended successfully, that is the punishment of the thief, then the description of the prison in the document was unnecessary. Therefore, the author used the materials, which illustrated the cases of escapes from the prisons. In addition to them, the researcher used the documents of the regimental offices, in which they requested permission from the capital authorities to carry out repair works.As a result of the study, it was found that the prisons of the regimental cities and Hlukhiv in the middle of the XVIII century usually consisted of a prison, an upper (1-2 huts) and a lower jail and a building for security. Sometimes houses of local residents were used to hold the prisoners. Regardless of the location of criminals, prisoners regularly suffered from the weather (cold, snow, rain). Not much better were the conditions for service in the guardians of the prisoners.Natural factors always destroyed wooden structures, even in the absence of fires. The fence around the prison and its walls over time were rubbed, and criminals were given the opportunity to escape. It is worth noting that the construction became much more unusable due to constant attempts to escape criminals. The practice of partial repair of prisons could not solve the problem, and for some time again, there was a need to upgrade the institution.According to the author, there were three ways of providing materials for the construction or repair of prisons. In the first case, resources were taken from the residents of the regiment on the basis of distribution, which was conducted by the regimental office with the consent of the capital authorities. In the second - the money from the treasury was used only for those materials that were not in the inhabitants of the regiment. The third option for carrying out repair works was that the state treasury assumed the funds for the purchase of all materials.
Keywords: Hetmanate; regimental cities; jail; prisoners; prison